Sex differences in adolescent physical aggression: Evidence from sixty‐three low‐and middle‐income countries. Issue 1 (3rd October 2018) - Nivette, Amy; Sutherland, Alex; Eisner, Manuel; Murray, Joseph
Abstract : A great deal of research shows that adolescent and adult males are more likely to engage in physical aggression and violence than females are. However, few studies have examined cross‐cultural variation in sex differences, particularly among low‐ and middle‐income countries [LMICs]. Based on social role and sexual selection theories, we derived two hypotheses regarding possible variations in sex differences across societal contexts: 1) sex differences increase with societal gender polarization (social role theory) and 2) sex differences are exacerbated in societies where socio‐economic opportunities are scarce, unequal, or insecure (prediction derived from sexual selection theory). The current study examined the prevalence of and variation in sex differences in physical aggression, as measured by frequent fighting, among 247, 909 adolescents in 63 low‐ and middle‐income countries. The results show that, overall, males were over twice as likely (OR = 2.68; 95% CI = 2.60–2.76) to report frequent fighting in the past 12 months than females. However, sex differences vary significantly across LMICs, wherein countries with higher female prevalence rates have smaller sex differences in frequent fighting. Contrary to expectations derived from social role theory, sex differences in physical aggression decrease as societal gender inequality increased. In regards to sexual selection theory, we find no evidence that sex differences in frequent fighting varies according to societal rule of law or income inequality.